2018
DOI: 10.5304/jafscd.2018.082.010
|View full text |Cite
|
Sign up to set email alerts
|

Soil Contaminant Concentrations at Urban Agricultural Sites in New Orleans, Louisiana: A Comparison of Two Analytical Methods

Abstract: Along with the many benefits of urban agriculture comes the possible exposure to contaminants not typically seen in rural soils. Through the use of standard laboratory analyses (ICP-AES and CVAAS) and a field-portable X-ray fluorescence spectrometer (XRF) calibrated for soil analysis, this study quantified contamination levels at urban agricultural sites throughout New Orleans, Louisiana. The results of the standard laboratory analyses were compared to the results from the XRF. We collected soil samples at 27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In soil, mercury is most commonly encountered in organic (Hg -C ) and inorganic (Hg 2+ ) forms (Lymberidi 2005;UNEP 2013), the presence of which affects the soil quality characteristics including natural soil profile and soil fertility values (Laker 2005). Since recent years the mercury contamination issue has become increasingly topical in regard to urban soils (Li et al 2010;Szymon Różański 2015;Gray et al 2015;Wan et al 2016;Kumar et al 2017;Moller et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In soil, mercury is most commonly encountered in organic (Hg -C ) and inorganic (Hg 2+ ) forms (Lymberidi 2005;UNEP 2013), the presence of which affects the soil quality characteristics including natural soil profile and soil fertility values (Laker 2005). Since recent years the mercury contamination issue has become increasingly topical in regard to urban soils (Li et al 2010;Szymon Różański 2015;Gray et al 2015;Wan et al 2016;Kumar et al 2017;Moller et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Next, the study results illustrate potential opportunities to reduce identified barriers to heavy metal soil testing. Development of rapid, low-cost soil testing tools [29,58,59] and partnership programs to make soil testing more accessible may influence some gardeners to test their soil. For example, universities, public health departments, citizen-scientists, and other organizations can collect and test soil samples, educate gardeners about the soil testing results, and provide training resources on gardening hazards [60,61,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement is the rst step to well understand the soil pollution in farmland, many scholars have conducted quite a number of research on the determination methods. At present, the laboratory analysis methods for element determination mainly include induced coupled plasma optical emission spectrometry (ICP-OES) (Oyourou et al 2019), induced coupled plasma mass spectrometry (ICP-MS) (Qu et al 2019; Pena-Ortega et al 2019), induced coupled plasma atomic emission spectrometry (ICP-AES) (Schneider et al 2016;Moller et al 2018;Wu et al 2012), AAS (Hu et al 2017), atomic uorescence spectrometry (AFS) (Qu et al 2018), and so on.…”
Section: Introductionmentioning
confidence: 99%